Structural characterisation and stability of new nanoquasicrystalline Al-based alloys - Galano, M; Audebert, F; Cantor, B; Stone, I (2004)
Nanoquasicrystalline Al-based alloys have been studied intensively for the last decade because of their promising mechanical properties. Recently quaternary nanoquasicrystalline alloys with improved thermal stability and better mechanical properties at elevated temperature have been reported. The present work describes an investigation into quaternary Al(93)Fe(3)Cr(2)Z(2) (at.%) (with Z = Ti, V, Nb, Ta) and ternary Al-93(Fe3Cr2)(7), produced by melt spinning. Structural characterisation was carried out by means of X-ray diffraction (XRD) and transmission electron microscopy (TEM), and the thermal stability and decomposition of the quasicrystalline phase were studied by means of differential scanning calorimetry (DSC). All of the alloys showed a microstructure consisting of spherical icosahedral particles embedded in an alpha-Al matrix. The fourth component produced a significant refinement of icosahedral particle size. The decomposition of the quaternary alloys was observed at higher temperatures than for the ternary alloy with a broad exothermic peak. The new alloys containing Nb and Ta showed a multimodal transformation process extending up to the onset of melting. lcosahedral particles containing Ta or Nb were observed after heat treatment at 550degreesC. (C) 2003 Elsevier B.V. All rights reserved.